Clinical applications of ultra-high field magnetic resonance imaging in multiple sclerosis. (4th March 2018) - Inglese, Matilde; Fleysher, Lazar; Oesingmann, Niels; Petracca, Maria
ABSTRACT: Introduction : Magnetic resonance imaging (MRI) is of paramount importance for the early diagnosis of multiple sclerosis (MS) and MRI findings are part of the MS diagnostic criteria. There is a growing interest in the use of ultra-high-field strength −7 Tesla- (7T) MRI to investigate, in vivo, the pathological substrate of the disease. Areas covered : An overview of 7T MRI applications in MS focusing on increased sensitivity for lesion detection, specificity of the central vein sign and better understanding of MS pathophysiology. Implications for disease diagnosis, monitoring and treatment planning are discussed. Expert commentary : 7T MRI provides increased signal-to-noise and contrast-to-noise-ratio that allow higher spatial resolution and better detection of anatomical and pathological features. The high spatial resolution reachable at 7T has been a game changer for neuroimaging applications not only in MS but also in epilepsy, brain tumors, dementia, and neuro-psychiatric disorders. Furthermore, the first 7T device has recently been cleared for clinical use by the food and drug administration.